A chromatin-based signalling mechanism directs the switch from mutagenic to error-free repair of DNA double strand breaks. (4th July 2019) - Bartke, Till; Groth, Anja
ABSTRACT: Mutations caused by DNA damage are a main driver of cancer. We discovered that recognition of newly synthesised histone H4 directs breast cancer type 1 susceptibility protein (BRCA1) to post-replicative chromatin. The switch from mutagenic to error-free DNA double strand break repair by homologous recombination is therefore controlled by chromatin.